Transporte aéreo: a inserção da região Nordeste brasileira nas artérias da globalização. - Moreira, Bruno Holtz da Nova (2007)
The present study deals with an analysis of the air transportation activity as factor of integration of the diverse regions of the globe, and its importance for the insertion of the Brazilian northeastern region in a global panorama. This thesis has for general objective a deep analyze the effect of the activity of air transportation on a new world, more integrated and interdependent. It has for specific objectives the analysis of the importance of this activity for the economic development of the Brazilian northeastern region. The work was lead in four stages: the first one makes an analysis of the concepts of logistic, the modal of transport,beyond a characterization of the activity of air transportation. The second stage turns on the importance of the air transportation for Brazil and connects the historical factors of the activity with the cycles of aviation. The third stage of the work aims at an analysis of the theoretical references of globalization concept and territory, searching to characterize the Brazilian northeast region. The fourth phase of thesis searches to demonstrate the importance for the northeast region in keeping an open channel of international communications by air with the Europe. After concluded the analysis, the thesis launches a series of proposals that culminate with forms of increment in the activity of the air transportation of perishable fruits and for the European continent, as well as the transformation of the northeast region in a second main gate of entrance and exit for international travelers.